Chapter Due autobiografie a confronto: Život i priključenija di Dositej Obradović e Žitije di Gerasim Zelić - Leto, Maria Rita (Biblioteca di Studi Slavistici, 2019)
Dositej Obradović's Život i priključenija is generally considered the symbolic herald of modern Serbian literature, a paradigmatic text which affected many later writers, including Gerasim Zelić. The paper compares Dositej's work and Zelić's Žitije focusing on three levels: firstly, it tracks the common topoi and the distinctive characteristics of the two texts; secondly, it discusses the ways in which Zelić reinterprets Dositej's model, especially with respect to autobiography and travelogue; finally, it elaborates on the different yet cognate notion of authorship the two texts propose.